(untitled) (Feni University Journal, 2026)
In Bangladesh and many other countries worldwide, managing registration and land ownership is extremely difficult. This method is extremely sluggish. Innovation with professional integrity and updated legislation is the key to a smart registration system in a state. An ownership change record from a sub-register office to a central database may not be updated for up to two years. E-procha, already available online and involves e-checking deeds of landed property transfer, will eradicate land transfer fraud and forgery. Comprehensive e-registration and information services, including e-registration of documents, property conveyance alert service, and automatic emutation, will contribute highly to these aspects. The Registration Act of 1908 needs to be reformed, which is a must to fulfill the era’s demands. Erroneous, forged, or twisted deeds result in thousands of civil suits in Bangladesh. An innovative and modern technology-based registration system can help remove the complications of land transactions today. FENI UNIVERSITY JOURNAL, 2024, 3(1), ISSN [2518-3869], PP. (211-222)